Impacts of three approaches on collaborative knowledge building, group performance, behavioural engagement, and socially shared regulation in online collaborative learning. - Zheng, Lanqin; Fan, Yunchao; Huang, Zichen; Gao, Lei (Journal of Computer Assisted Learning, 2024)
Background: Online collaborative learning has been widely adopted in the field of education. However, learners often find it difficult to engage in collaboratively building knowledge and jointly regulating online collaborative learning. Objectives: The study compared the impacts of the three learning approaches on collaborative knowledge building, group performance, socially shared regulation, behavioural engagement, and cognitive load in an online collaborative learning context. The first is the automatic construction of knowledge graphs (CKG) approach, the second is the automatic analysis of topic distribution (ATD) approach, and the third one is the traditional online collaborative learning (OCL) approach without any analytic feedback. Methods: A total of 144 college students participated in a quasi‐experimental study, where 48 students learned with the CKG approach, 48 students used the ATD approach, and the remaining 48 students adopted the OCL approach. Results and Conclusions: The findings revealed that the CKG approach could encourage collaborative knowledge building, socially shared regulation, and behavioural engagement in building knowledge better than the ATD and OCL approaches. Both the CKG and ATD approaches could better improve group performance than the OCL approach. Furthermore, the CKG approach did not increase learners' cognitive load, but the ATD approach did. Implications: This study has theoretical and practical implications for utilising learning analytics in online collaborative learning. Furthermore, deep neural network models are powerful for constructing knowledge graphs and analysing topic distribution. Lay Description: What is currently known about the subject matter: Online collaborative learning has been widely adopted in the field of education.Learners often find it difficult to engage in collaboratively building knowledge and jointly regulating collaborative learning. What the paper adds to this: This study compared the impacts of three learning approaches, namely, the automatic construction of knowledge graphs (CKG), the automatic analysis of topic distribution (ATD), and the traditional online collaborative learning (OCL) approach.The findings revealed that the CKG approach could encourage collaborative knowledge building, socially shared regulation, and behavioral engagement in building knowledge better than the ATD and OCL approaches. Both the CKG and ATD approaches could better improve group performance than the OCL approach. Furthermore, the CKG approach did not increase learners' cognitive load, but the ATD approach did. Implications of study findings for practitioners: It is strongly recommended that the CKG approach can be employed to enhance collaborative knowledge building, socially shared regulation, and behavioral engagement in building knowledge in an online collaborative learning context. Both the CKG and ATD approaches contribute to improving group performance.Deep neural network models are powerful for constructing knowledge graphs and analysing topic distribution.